KRITIK SOSIAL DALAM PUISI â€œKARANGAN BUNGAâ€ KARYA TAUFIK ISMAIL - Krisna, Avni Amelia Putri; Qur'ani, Hidayah Budi (Universitas Tanjungpura, 2021)
AbstractLiterary work, especially poetry, is an effective form of work in delivering social criticism. Literary works often describe the social reality that exists around the author's environment. Taufik Ismail's literary works carry a lot of themes that are full of social criticism in the life problems of the Indonesian people. In addition to the theme of social criticism, Taufik Ismail's poetry literature also focuses on moral, social, political, cultural, love, and religious themes. The objective of this research is to describe the social criticism contained in the poem